PERANCANGAN STRUKTUR ATAS JEMBATAN SUNGAI MESIM MENGGUNAKAN RANGKA BAJA BERDASARKAN SNI 1725:2016 - Layla Kumala Rizki; Indriyani Puluhulawa (LPPM Universitas Abdurrab, 2021)
One of rivers on Rupat Island is Mesim River. The bridge crosses the river is a reinforced concrete bridge. Accordance with Bina Marga regulations for 40 – 200 m long obstacles, steel truss bridge is the most economical type. Therefore, in this planning the author redesigned upper structure of Mesim River Bridge using a steel truss. This design aims to obtain effective upper structur dimension, implementation steps and engineer of estimate. This plan refers to SNI 1725:2016 about bridge loading, RSNI T-03-2005 about steel structure planning for bridges, and SNI T-12-2004 about concrete structure planning. This bridge is planned with a length of 52 m. Based on planning results, the bridge slab thickness is 200 mm, stringer uses IWF 350.175.7.11, cross girder uses IWF 700.300.13.24, main truss uses IWF 400.400.13.21